ANALISIS IDENTIFIKASI KONDISI STRUKTUR BANGUNAN - Azaria Andreas; Ayu Herzanita; Resti Nur Arini (Jurnal JANATA, 2023)
In order to carry out maintenance and upkeep activities, the first thing that must be done is to identify the condition of the building while paying attention to the various causes of damage that occurs and plans for future use of the building. The Master of Management Building, Faculty of Economics and Business, Pancasila University is a building that is more than 20 years old and requires repairs. Structural damage investigations are needed to assess building damage to determine the level of damage as an initial step in the process of identifying the level of building damage. This activity aims to assess the level of damage at the case study location. The initial stage of assessing the level of damage is carried out by carrying out visual observations of all building components. This research uses a descriptive qualitative approach which focuses on identifying the condition of the building structure. The data collection process was carried out by field observation and interviewing respondents (staff, employees, lecturers, work units at the study location, and faculty leaders) to find out the building's previous function and future plans. Analysis of the condition of the building structure and formulation of follow-up recommendations is prepared by involving experts (building structural experts). The research results showed that from visual observations, no damage was found, especially to the structural elements of the building. However, to plan to restore the building's function, a number of follow-up efforts are required, such as carrying out tests using the Non-Destructive Test (NDT) method, strengthening several structural elements including installing foundations on additional structural parts, and replacing the shape and material of the roof covering.